(N~ERTY STILQ d(B, (N{OSTAKOWI^As (NsBORNIK TEORETI^ESKIH STILEJ(B.s ((NmOSKWAs (NsOWETSKIJ KOMPOZITORs, 1962)
(NsBORNIK (B"(N~ERTY STILQ d(B.(N{OSTAKOWI^A (B"(NQWLQETSQ PERWYM WYPUSKOM SOBRANIQ TEORETI^ESKIH STATEJ(B.(NPOSWQ]ENNYH ISSLEDOWANIJ TWOR^ESTWA d(B.(Nd(B, (N{OSTAKOWI^As
Keywords: (NmONOGRAFIQs